Effect of Nitrobenzene on Morphometric Indices of Rat Testes Under Cold Stress - Bachinsky, R. O.; Shcholok, Tetiana S.; Molchanova, Anna V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 166